1997 Turfgrass Research - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
With our staff at full strength, several new research projects have been initiated for the 1997 season. As always, we are anxious to hear your suggestions for research that can be done to improve our ability to maintain healthy turf in Kansas.
Keywords: Turfgrass; Environmental stress; Pest management; Creeping Bentgrass; Bluegrass; Ryegrass; Fescue